Windows 8.1 : the missing manual - Pogue, David, 1963- (Missing manual., 2013)
Windows 8.1 continues the evolution of the most radical redesign in Microsoft's history. It combines the familiar Windows desktop with a new, touchscreen-friendly world of tiles and full-screen apps. Luckily, David Pogue is back to help you make sense of it--with humor, authority, and 500 illustrations. The important stuff you need to know: What's new in 8.1. The update to 8.1 offers new apps, a universal Search, the return of the Start menu, and several zillion other nips and tucks. New features. Storage Spaces, Windows To Go, File Histories--if Microsoft wrote it, this book covers it. Security. Protect your PC from viruses, spyware, spam, sick hard drives, and out-of-control kids. The network. HomeGroups, connecting from the road, mail, Web, music streaming among PCs--this book has your network covered. The software. Media Center, Photo Gallery, Internet Explorer, speech recognition--this one authoritative, witty guide makes it all crystal clear. It's the book that should have been in the box.